Association between estimated fluoride intake and dental caries prevalence among 5-year-old children in Korea. Issue 1 (December 2015) - Kim, Min-Ji; Kim, Han-Na; Jun, Eun-Joo; Ha, Jung-Eun; Han, Dong-Hun; Kim, Jin-Bom
Abstract Background The purposes of this study were to estimate the fluoride intake from food and drink in 5-year-old Korean children, and to measure the association between estimated fluoride intake and dental caries prevalence. Methods The study involved a secondary analysis of raw data from the 4th Korea National Health and Nutrition Examination Survey (KNHANES; 2007–2009). The study subjects were 167 boys and 147 girls aged 5 years who had undergone both physical and nutritional examination as part of the survey. The KNHANES comprised a health questionnaire, a physical examination, and a nutritional examination. The nutritional examination of KNHANES consisted of 3 parts: a dietary life survey, a food-frequency questionnaire, and a food intake investigation. The food intake investigation used the 24-h recall method, with information being provided by the children's parents. On the basis of this information, we evaluated the fluoride content in a total of 310 food items using the hexamethyldisiloxane (HMDS)-facilitated diffusion method, modified using Taves' microdiffusion method. As part of the KNHANES survey, oral examinations were conducted at a mobile examination centre by trained dentists using dental mirrors under a fluorescent light. These examinations were performed using methods proposed by the World Health Organization. Results The dietary fluoride intake of 5-year-old Korean children was estimated to be 0.35 mg/day, or 0.016 mg/kg/day. The "decayed or filled surfaces" (dfs) indices of primary teeth were higher in children who had a lower dietary intake of fluoride. There was a significant inverse association between dietary fluoride intake and the prevalence of dental caries. Conclusion The inverse association between dietary fluoride intake levels and prevalence of dental caries implies that the introduction of community caries prevention programmes may be beneficial. Such programmes would include water fluoridation and a fluoride supplementation programme.